2020
DOI: 10.1002/jaba.712
|View full text |Cite
|
Sign up to set email alerts
|

Training class inclusion responding in individuals with autism: Further investigation

Abstract: Class inclusion (CI) requires responding to an item simultaneously as a member of both a class and a more inclusive class that contains that class. This study extends previous research by Ming et al. (2018) who trained CI responding in typically developing children and individuals with autism using a Relational Frame Theory (RFT) approach according to which CI involves responding in accordance with relations of containment and comparison. In Ming et al., participants experienced multiple exemplar training in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
2
0
4
Order By: Relevance
“…Foi possível observar, a partir de diversas evidências (Slattery et al, 2011, Gil et al, 2012 como as propriedades definidoras do RRAA são observadas nesse tipo de moldura relacional, especialmente a transformação de função e a assimetria esperada em diferentes níveis hierárquicos. Além disso, esses trabalhos também procuraram investigar variáveis características deste tipo de repertório, consideradas importantes a partir de outras bases teóricas, como o pertencimento de classe transitiva, pertencimento de classe assimétrica e indução unilateral de propriedades (Slattery & Stewart, 2014) ou mesmo a inclusão de classes (Ming et al, 2018;Zagrabska-Swiatkowska et al, 2020). Os resultados observados ressaltaram o potencial e a precisão da explicação baseada em molduras relacionais de hierarquia.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Foi possível observar, a partir de diversas evidências (Slattery et al, 2011, Gil et al, 2012 como as propriedades definidoras do RRAA são observadas nesse tipo de moldura relacional, especialmente a transformação de função e a assimetria esperada em diferentes níveis hierárquicos. Além disso, esses trabalhos também procuraram investigar variáveis características deste tipo de repertório, consideradas importantes a partir de outras bases teóricas, como o pertencimento de classe transitiva, pertencimento de classe assimétrica e indução unilateral de propriedades (Slattery & Stewart, 2014) ou mesmo a inclusão de classes (Ming et al, 2018;Zagrabska-Swiatkowska et al, 2020). Os resultados observados ressaltaram o potencial e a precisão da explicação baseada em molduras relacionais de hierarquia.…”
Section: Discussionunclassified
“…Os procedimentos realizados por Mulhern et al, (2017;, Ming et al, 2018;Zagrabska-Swiatkowska et al (2020) incluíram sempre como participantes crianças, e em alguns destes estudos crianças com atrasos no desenvolvimento. Além disso, trabalhos como o de Gil et al (2012; e Slattery e Stewart (2014) possuem procedimentos relativamente pontuais que poderiam ser facilmente adaptáveis para crianças com desenvolvimento típico ou atípico.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Gil et al (2012Gil et al ( , 2014 demonstrated the bottomup transformation of functions through hierarchical networks that included relations of coordination and distinction. As well, recent research has shown that class-inclusion responses can be trained through a nonarbitrary MET in autistic individuals (Zagrabska-Swiatkowska, Mulhern, Ming, Stewart, & McElwee, 2020). Finally, two very recent studies have systematically demonstrated the contextual control in hierarchical responding at two levels (Callejón, 2020;Villarroel, Luciano, & Ruiz-Sánchez, 2021).…”
Section: Evidence Of the Transformation Of Eliciting And Avoidance Functionsmentioning
confidence: 95%